The Effects of Individualized Information and Emotional Support Education on Midwifery Students’ Anxiety during the COVID-19 Pandemic - Zehra Baykal Akmeşe; Birsen Karaca Saydam; Güzin Kardeş (Medicina, 2022)
Background and Objectives: Midwifery students were not able to participate in internship programs and related practices during the COVID-19 pandemic. This kept them from meeting graduation requirements because they could not do the one-on-one observations for clinical case management. In this study, we aim to determine the effects of Individualized Information and Emotional Support Education (IESE) on the midwifery students’ anxiety levels during the COVID-19 pandemic. Materials and Methods: This is an experimental study with two stages. In the first stage, the researchers determined the anxiety levels of 268 students. In the second stage, 76 students with high levels of anxiety were provided with IESE. The IESE was conducted in interviews on online platforms and took a minimum of 60 min. The students’ anxiety levels were measured again one week after the IESE. Results: Statistically significant differences were found between the students’ State Anxiety Scale scores before and after the IESE (t = 8.756, p = 0.000). Before the IESE, 65.8% of the students had high anxiety levels about COVID-19-related disease or death, and the possibility of losing loved ones. After the education, this rate fell by 17.1% to 48.7%, and this difference was significant (χ2 = 5.077, p = 0.024). Conclusions: The IESE positively affected the students’ anxiety levels. Even just showing interest can make people feel cared for and valued, and people are sensitive to their needs. After this study, 30 students with high anxiety levels were sent for consultation with an expert and have been followed up by researchers.